Investigation of the Usage of Depolymerized Nylon 66 Intermediate in Phenolic Resin Modification. Issue 4 (4th March 2019) - Emik, Serkan; Yılmaz, Burcu Yasemin; İyim, Tülin Banu
ABSTRACT: In this study, the potential usage of the Nylon 66 hydrolysis products (HP) for curing "high ortho" novolac resin (N) was investigated. According to FTIR, DSC and TGA results, it is concluded that HP can be as a curing agent for N without the need for another crosslinking agent and thermal degradation stability of cured N-HP blends increased significantly up to 15% HP content. Furthermore, according to performed surface coating tests, it is shown that all films prepared with HP up to 30-wt % have excellent water resistance, drying and adhesion properties as well as with high hardness values.